Synthesis and spectroscopic characterization of new metal(II) complexes with methionine sulfoxide - Massabni, Antonio C. [UNESP]; Corbi, Pedro P. [UNESP]; Melnikov, Petr; Zacharias, Marisa A.; Rechenberg, Hercílio R. (Taylor & Francis, 2004)
Methionine sulfoxide complexes of iron(II) and copper(II) were synthesized and characterized by chemical and spectroscopic techniques. Elemental and atomic absorption analyses fit the compositions K2[Fe(metSO) 2]SO4 · H2O and [Cu(metSO)2] · H2O. Electronic absorption spectra of the complexes are typical of octahedral geometries. Infrared spectroscopy suggests coordination of the ligand to the metal through the carboxylate and sulfoxide groups. An EPR spectrum of the Cu(II) complex indicates tetragonal distortion of its octahedral symmetry. 57Fe Mössbauer parameters are also consistent with octahedral stereochemistry for the iron(II) complex. The complexes are very soluble in water.
Keywords: Amino acids; Copper(II); Iron(II); Methionine sulfoxide; carboxylic acid; coordination compound; copper complex; iron complex; metal complex; methionine sulfoxide; potassium; sulfate; sulfoxide; water; atomic absorption; chemical composition; chemical structure; elemental analysis; geometry; infrared spectroscopy; Mossbauer spectroscopy; solubility; spectroscopy; stereochemistry; synthesis